AI-Based Feedback in German as a Foreign Language Classes: Relevance and Impact on Learners' Writing Skills. - Dwi Putri Ningsih (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2026)
The use of artificial intelligence (AI) in foreign language teaching is a widely discussed topic among educators. Some are concerned that learners will become too dependent on AI tools, making it difficult for teachers to assess their actual language proficiency. However, recent studies (e.g. Schluer, 2024) demonstrate that AI-Based Feedback can serve as an effective 'teaching assistant’. This research analyses the importance and effectiveness of AI feedback in German as a foreign language instruction for beginners. The focus is on the influence of automatic feedback on writing proficiency. The study examines the opportunities and risks of this technology. It demonstrates how teachers can use AI tools to support the learning process while enabling learners to write independently. The result showed that AI- Based Feedback helps learners to study more independently. However, this is only the case if the tools — in this instance, AI bots — are used in a controlled manner. A critical point is that overly complicated corrections can overwhelm learners.